The burden of modernity : the rhetoric of cultural discourse in Spanish America - Alonso, Carlos J. (OUP E-Books., 1998)
An interpretation of cultural discourse in Spanish America which argues that Spanish American cultural production is marked by an internal rhetoric crisis that resulted from the adoption of discourses regarded as modern in historical and economic circumstances that are, in fact, the negation of modernity.